Partially Covered Metal Stents May Not Prolong Stent Patency Compared to Uncovered Stents in Unresectable Malignant Distal Biliary Obstruction - Kim, Jae Yun; Ko, Gyu Bong; Lee, Tae Hoon; Park, Sang-Heum; Lee, Yun Nah; Cho, Young Sin; Jung, Yunho; Chung, Il-Kwun; Choi, Hyun Jong; Cha, Sang-Woo; Moon, Jong Ho; Cho, Young Deok; et al. (Gut and liver, 2017)
Background/Aims: Controversy still exists regarding the benefits of covered self-expandable metal stents (SEMSs) compared to uncovered SEMSs. We aimed to compare the patency and stent-related adverse events of partially covered SEMSs (PC-SEMSs) and uncovered SEMSs in unresectable malignant distal biliary obstruction. Methods: A total of 134 patients who received a PC-SEMS or uncovered SEMS for palliation of unresectable malignant distal biliary obstruction were reviewed retrospectively. The main outcome measures were stent patency, stent-related adverse events, and overall survival. Results: The median stent patency was 118 days (range, 3 to 802 days) with PC-SEMSs and 105 days (range, 2 to 485 days) with uncovered SEMSs (p=0.718). The overall endoscopic revision rate due to stent dysfunction was 36.6% (26/71) with PC-SEMSs and 36.5% (23/63) with uncovered SEMSs (p=0.589). Tumor ingrowth was more frequent with uncovered SEMSs (4.2% vs 19.1%, p=0.013), but migration was more frequent with PC-SEMSs (11.2% vs 1.5%, p=0.04). The incidence of stent-related adverse events was 2.8% (2/71) with PC-SEMSs and 9.5% (6/63) with uncovered SEMSs (p=0.224). The median overall survival was 166 days with PC-SEMSs and 168 days with uncovered SEMSs (p=0.189). Conclusions: Compared to uncovered SEMSs, PC-SEMSs did not prolong stent patency in unresectable malignant distal biliary obstruction. Stent migration was more frequent with PC-SEMSs. However, tumor ingrowth was less frequent with PC-SEMSs compared to uncovered SEMSs. KCI Citation Count: 11